Cardiac Autonomic Function Measured by Heart Rate Variability and Turbulence in Pre-hypertensive Subjects. (April 2013) - Erdem, Alim; Uenishi, Masahiro; Küçükdurmaz, Zekeriya; Matsumoto, Kazuo; Kato, Ritsushi; Hara, Motoki; Yazıcı, Mehmet
<x xml:space="preserve">Abstract</x> Non-dipping blood pressure pattern was shown to be associated with increased cardiovascular events. In addition, cardiac autonomic dysfunction was found to be associated with non-dipper phenomenon. In this study, we aimed to evaluate the cardiac autonomic functions in dipper and non-dipper pre-hypertensive subjects. A total of 65 pre-hypertensive subjects were enrolled in this study. They were divided into two groups as non-dippers (40 subjects, 52% female) and dippers (25 subjects, 52.5% female). Cardiac autonomic functions of the two groups were compared with the aid of heart rate variability, heart rate turbulence (HRT), atrial premature contractions (APCs), ventricular premature contractions (VPCs), and mean heart rate (MHR). There was no significant difference between non-dippers and dippers in basal characteristics. The two parameters of HRT, turbulence onset and turbulence slope, were found to be significantly abnormal in non-dippers than in dippers (P < .011 and P < .002, respectively). Heart rate variability parameters, including SDNN, SDANN, RMSSD, and pNN50, were found to be similar in dipper and non-dipper pre-hypertensive subjects (P < .998, P < .453, P < .205, and P < .788, respectively). APCs, VPCs, and MHR were compared, and there were statistical differences between the groups (APCs 5.80 ± 4.55, 9.14 ± 7.33, P < .024; VPCs 8.48 ± 8.83, 13.23 ± 9.68, P < .044; and MHR 70.16 ± 11.08, 76.26 ± 11.31, P < .035; respectively). This study demonstrated a possible cardiac autonomic dysfunction in pre-hypertensive subjects with non-dipper pattern. This may be a basis for future studies related to pre-hypertension and non-dipping BP pattern.